PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MODIFICATION NUMBERED HEADS BERBANTUAN MEDIA KARTU DALAM PEMBELAJARAN BAHASA INDONESIA KELAS VI SD SWASTA AL-AZHAR BUKITTINGGI - MEGASARI MARTIN (Inovasi Pendidikan, 2017)
Indonesian Language Learning in Primary School has not been taught optimally in guiding students to be active and master the material.One of the less-than-optimal learning is about raw vocabulary material. In learning standard vocabulary there are still many students who encountered difficulties in determining the use of standard vocabulary in a sentence.For that need a solution to fix the problem, one solution is to apply learning models that are assisted learning media.One of the learning models that provide learning process activities that demand the active student is the cooperative type.In addition, the media also have an important role to the understanding of raw vocabulary material. Media is expected to help at the same time become interesting and fun in learning the standard vocabulary.Card media is a medium that can be used in learning standard vocabulary.Using the media card, will provide understanding and habituation in the introduction of raw vocabulary. The goal to be achieved from this effort is to apply the cooperative model of co-assisted media card. This application research using cooperative model type Modified Numbered Heads aided media card in learning Indonesian language. Data types are primary and secondary data. Sampling method using purposive sampling. Data collection uses observation, tests, and interviews. The research instrument is an observation sheet and a learning result test. Data processing analyzed data of learning result is done by test of equality of two mean. Then, hypothesis testing is done to determine whether the learning outcomes of Indonesian class VI A given the application of better with no application.Keywords: Modification Numbered Heads, Media Card